Developing a blended learning based model for teaching foreign languages in engineering institutions; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Kudryashova A. V. Aleksandra Vladimirovna (2016, 2016)
Title screen